The Influence of Product Innovation, Celebrity Endorsers and Tagline toward Purchase Intention with Brand Awareness as The Mediating Variable - Safrilia, Safrilia Putri B1024141001 (Jurnal Manajemen Update, 2018)
ABSTRACT             Product Innovation become an important aspect in order to make the company survive in this massive competition. Every company are trying to serve product which is unique and catchy that can distinguish their product from the other company. Celebrity Endorsers are used to make society attract to the product and used to delivered the advertising message or recommends buying a product. Beside using celebrity endorsers, company are competing in making tagline for its products to captures a company’s brand essence, personality and positioning also distinguishes the company from its competitors. Celebrity Endorsers and Tagline which can be found on the advertisement to provide experience and impression while product innovation provides the improvement through innovation of the products to audience which expected to increase brand awareness and taking an important place for customer purchase intention of the product. This study aims to analyze the influence of Product Innovation, Celebrity Endorsers, and Tagline in the context of Purchase Intention of VIVO V9 in Pontianak with Brand Awareness as The Mediating Variable.            The sample of this study consists of 100 respondents who are pontianak residents and at least age 18 years old. The data were analyzed in Structural Equation Model Partial Least Square using SmartPLS 3.2.7 software. It is found that Product Innovation, Celebrity Endorsers and Tagline has positive relationship on Brand Awareness. Product Innovation and Celebrity Endorsers do not have positive relationship on Purchase Intention, while Tagline has positive relationship on Purchase Intention. The mediation role of Brand Awareness between Product Innovation and Purchase Intention is fully mediated, Celebrity Endorsers and Purchase Intention is also fully mediated and Tagline and Purchase Intention is partially mediated.Keywords: Product Innovation, Celebrity Endorsers, Tagline, Brand Awareness Purchase Intention ABSTRAK Inovasi Produk menjadi aspek penting untuk membuat perusahaan bertahan dalam kompetisi besar ini. Setiap perusahaan berusaha untuk menyajikan produk yang unik dan menarik yang dapat membedakan produk mereka dari perusahaan lain. Celebrity Endorsers digunakan untuk membuat masyarakat tertarik pada produk dan digunakan untuk menyampaikan pesan iklan atau merekomendasikan untuk membeli suatu produk. Selain menggunakan celebrity endorsers, perusahaan berlomba-lomba membuat tagline untuk produknya untuk menangkap esensi, kepribadian, dan posisi merek perusahaan juga membedakan perusahaan dari pesaingnya. Celebrity Endorsers dan Tagline yang dapat ditemukan di iklan untuk memberikan pengalaman dan kesan sementara inovasi produk memberikan peningkatan melalui inovasi produk ke audiens yang diharapkan dapat meningkatkan kesadaran merek dan mengambil tempat yang penting untuk tujuan pembelian pelanggan dari produk. Penelitian ini bertujuan untuk menganalisis pengaruh dari Inovasi Produk, Celebrity Endorsers, dan Tagline dalam konteks Minat Beli VIVO V9 di Pontianak dengan Kesadaran Merek sebagai Variabel Mediasi.Sampel penelitian ini terdiri dari 100 responden yang tinggal di kota pontianak dan berusia minimal 18 tahun. Data dianalisis dalam Structural Equation Model Partial Least Square menggunakan perangkat lunak SmartPLS 3.2.7. Ditemukan bahwa Inovasi Produk, Celebrity Endorsers, dan Tagline memiliki hubungan positif pada Kesadaran Merek. Inovasi Produk dan Celebrity Endorser tidak memiliki hubungan positif pada Minat Beli, sedangkan Tagline memiliki hubungan positif pada Minat Beli. Peran mediasi Kesadaran Merek antara Inovasi Produk dan Minat Beli sepenuhnya dimediasi, Celebrity Endorsers dan Minat Beli juga sepenuhnya dimediasi dan Tagline dan Minat Beli secara mediasi parsial. Kata Kunci: Inovasi Produk, Celebrity Endorsers, Tagline, Niat Beli Kesadaran Merek